Pengaruh intensitas cahaya biru yang berbeda terhadap pertumbuhan dan kelangsungan hidup benih ikan kerapu cantang (Epinephelus fuscoguttatus lanceolatus) - Seran, Fransiskus Devensius; Lukas, Ade Yulita Hesti; Linggi, Yulianus (Nusa Cendana University, 2024)
This research was conducted to determine the distance of blue light lamp placement above the water surface can affect the growth of grouper cantang (Epinephelus fuscoguttatu lanceolatus). A completely randomized design method was used with the test fish distributed to 12 aquariums. There were 3 treatment conditions and 3 replications. Treatment A with light intensity of 15 Lux, treatment B with light intensity of 25 Lux, and treatment C with light intensity of 35 Lux. The research was carried out for 30 days at the Faculty of Marine Animal Husbandry and Fisheries, Nusa Cendana University. Installation of blue lights with different placement distances was carried out in each research unit. The test animals used were 6-8cm with uniform size. Keywords: Light, grouper, survival rate, growth, survival rate.